Gut microbiota and body weight : a review - Duca, Ioana (Array, 2018)
The link between gut microbiota and insulin resistance has an important clinical impact, people affected by dysbiosis having a predisposition for developing: obesity, type 2 diabetes mellitus, nonalcoholic fatty liver disease, cancers, cardiovascular, neurodegenerative and psychiatric diseases. Dysbiosis may lead through chronic inflammation to obesity and metabolic syndrome. We carried out a systematic review of the studies dedicated to the role of gut microbiota in weight gain and obesity. A systematic literature search of recent data published in electronic databases, was performed, using as search phrase: "gut microbiome and body weight and obesity". Studies that contained no data about the influence of gut microbiota changes on obesity were excluded. Western diet, antibiotic use in childhood, excessive maternal pre-pregnancy weight, Cesarean delivery, and testosterone deficiency are triggers of the alteration of microbiota and subsequently the appearance of obesity. Predominance of Firmicutes and anaerobic genera, changes in the mycobiome and viral intestinal population are implied in the etiology of obesity. Prebiotics, polyphenols, different herbs, medication (antidiabetics, calcium), physical exercise, rich fibre intake and bariatric surgery are the most important therapeutic options. Personalized dietary treatments, antiviral agents and mycobiome manipulation would represent the new target in treating obesity. Any change of the quantitative and qualitative composition of microbiota has influence on the components of metabolic syndrome, so any management strategy for the treatment or prevention of obesity in children and adulthood should have the microbiome as target.